Surviving without a secretary : guide to personal productivity - Manzo, Jean Quinn (Crisp Pub. Menlo ParkUS, 1996)
Provides 50 practical tips to assist managers who must work without personal secretaries, and therefore need to acquire additional skills. Deals with areas including: keyboarding skills; dealing with the public; time management; and e-mail management.